Species identification of processed sea cucumbers from Malaysian market based on concatenated gene sequences of mitochondrial rRNA genes - Kamarudin, Kamarul Rahim; Mohamed Rehan, Maryam; Mohamed Rehan, Aisyah (Faculty of International Maritime Studies, Kasetsart University, 2019)
Species identification of sea cucumbers that have undergone body deformation due to extensive food processing e.g. beche-de-mer is difficult especially with the copresence of cases of unlabelled or mislabelled sea cucumber-based products in the markets. Therefore, a study was done to determine the species identities of processed sea cucumbers from selected Malaysian markets using concatenated gene sequences of non-protein-coding 12S and 16S mitochondrial rRNA genes. Phylogenetic analyses based on the distance-based Neighbour Joining method, and the character-based methods i.e. the Maximum Parsimony method, Maximum Likelihood method, and the Bayesian Analysis method of 47 ingroup sequences representing 37 processed sea cucumber specimens, 6 reference samples, and 4 additional specimens suggested the presence of 3 main clusters i.e. gamat family consisting of genus Stichopus and genus Thelenota; and timun laut family comprising family Holothuriidae. A number of 3 gamat species i.e. Stichopus horrens, Stichopus vastus, and Thelenota anax were recorded. Meanwhile, the specimens of Holothuria (Halodeima) atra, Holothuria (Halodeima) edulis, Holothuria (Metriatyla) lessoni, Holothuria (Mertensiothuria) leucospilota, and Holothuria (Metriatyla) scabra were the 5 timun laut species that grouped under the family Holothuriidae. The outcomes of this study can be utilised by the enforcement agencies to monitor and overcome the issues of species substitution and product mislabelling of processed sea cucumber products in Malaysian markets.